Eurasia: Second Asia-Europe Dance Forum Mapping Some SIte of Mis/Understanding - Helly Minarti (Wacana Seni Journal of Arts Discourse, 2006)
Since it was frrst organized in 2002. the Asia Europe Dance Forum (AEDF) has become a reguJar programme of the Asia Europe Foundation (ASEF). The original idea was to provide a meeting platform for young cboreographers trom Asia and Europe that alternately takes place in one member country of the two continents every year. For each year, ASEF would look for a partner organisation in member countries in either Europe or Asia countries lo co-hold the event. In 2002, it was Singapore's Goelbe-Institut: no partnership was secured; 2004 in Berlin with Hebbel am Ufer Theater; 2005 in Tokyo with Tokyo Performing Arts Market (TPAM) and Dance and Media; 2006 in Warsaw with Cinema Arts Foundation, On/Off Productions and Egurrola Dance Studio (forthcoming). Next year will be the turn of Beijing, partnering with the China Dance Association.